Printed Wearable Electronics: Recent Development of Printed Micro‐Supercapacitors: Printable Materials, Printing Technologies, and Perspectives (Adv. Mater. 3/2020). Issue 3 (21st January 2020) - Li, Hongpeng; Liang, Jiajie
Abstract : In article number 1805864, Jiajie Liang and Hongpeng Li review the recent progress in the preparation of functional ink systems for printed and wearable micro‐supercapacitors (MSCs), encompassing electrode materials, conductor materials, and electrolytes. Various issues that hinder the full materialization of widespread adoption of printed MSCs, the next steps to overcome these issues, and an in‐depth analysis of further scientific and technical challenges are also discussed.